Christian Motives in Selected Works with Homosexual Themes in Czech Literature - Mašát, Milan (Universitas Sanata Dharma, 2023)
The main aim of the paper is to highlight the relationship between Christianity and homosexuality based on selected fiction texts by Czech writers and poets (Zeyer, Fuks, Kuběna, Georgiev). The selected authors represent different historical periods and different currents of opinion. We are convinced that the theoretical part provides a suitable methodological basis for the part of the paper in which we discuss homosexual motives in selected works of the mentioned authors. To sum up, we can state that the explicit expression of homoerotic and other motives is only relevant today; in artistic narratives dating back to the 19th and 20th centuries, these symbols are expressed in a hidden way, and it is up to each recipient to decide whether and to what extent they see them in these narratives. Zeyer could not fully express himself; he was forced to use hidden symbols to be who he felt he was, at least in his works. Kuběna, in the context of the 1970s, treats the topic of homosexuality very openly, he is not afraid of being condemned by society. Fuks´ works are characterized by a considerable degree of autobiography. Despite Georgiev´s clear rejection of faith, a believing homosexual appears more than once in his work. In this paper we try to fill a certain gap in the field of comparative research in works of art and poems by authors who in some way tended to homosexuality because within the Czech context, we have encountered this area of scholarly articles sporadically.